EVALUASI PELAKSANAAN KEBIJAKAN PEMERINTAH TENTANG REVITALISASI PASAR KEMBANG KALISARI - Dian Kristina Prianingrum; Priyatno Harsasto (Journal of Politic and Government Studies, 2019)
This research was conducted to explain the efforts of the Semarang City Government in relation to policy evaluation regarding the revitalization of the Kalisari Flower Market. The research on "Evaluating the Implementation of Government Policy on the Revitalization of Kalisari Flower Market" with a Case Study in Kalisari Flower Market in Semarang City uses Qualitative research methods with a descriptive approach to find out what is the direct impact of Kalisari Flower Market Revitalization as a monitoring and evaluation process, and find further solutions to the problems faced after revitalization. The results of the research show that the local government of Semarang City always strives to provide a policy solution for the community, especially the object of policy, namely the traders in Kalisari Flower Market as a form of evaluation of the previous policy of Kalisari Flower Market Revitalization. The effort was proven in the Kalisari Phase III Flower Market Development plan, namely the addition of a Canopy on the back side which later served as a land for craftsmen to carry out flower arrangement activities so that flower arrangement activities were no longer in the sidewalk area so that the comfort of the sidewalk users or foot guarantee.Keywords: Efforts, Policy, Evaluation, Revitalization, Public Facilities